Intention to Use Financing Products of Muamalat Banks in Polewali Mandar - Halipah Halipah; Yeny Fitriyani; Purwanto Purwanto; Milna Wafirah (Department of Islamic Economic, Faculty of Economic and Business, Nahdlatul Ulama Islamic University (UNISNU) Jepara, Indonesia, 2022)
This study aims to examine the effect of attitudes, subjective norms, and knowledge of the intention to use Muamalat bank financial products in Kabupaten Polewali Mandar. Data collection and information needed in this study are primarily data where data obtained directly from the research subjects in the form of questionnaires. This study uses the Theory of Planned Behavior (TPB) and linear regression analysis. This study's results indicate the influence simultaneously and partially on the variable attitude, subjective norms, and knowledge of the intention to use Muamalat bank financial products.